Right‐sided aortic arch and aberrant left subclavian artery with or without a left nonrecurrent inferior laryngeal nerve. Issue 10 (30th April 2016) - Masuoka, Hiroo; Miyauchi, Akira; Higashiyama, Takuya; Yabuta, Tomonori; Kihara, Minoru; Miya, Akihiro
ABSTRACT: Background: In thyroid surgery, preserving the recurrent laryngeal nerve (RLN) is crucial for preventing postoperative phonatory dysfunction. Right nonrecurrent laryngeal nerves (NRLNs) are not particularly rare, and they are vulnerable to injury during surgery. This anomaly is associated with a right aberrant subclavian artery. Thus, a right‐sided aortic arch with an aberrant left subclavian artery (LSA) suggests a possible left NRLN. Methods: We report the cases of 4 patients with right‐sided aortic arch and aberrant LSA. Preoperative imaging studies revealed those anomalies, but no signs of situs inversus. During the surgeries, only 1 of the 4 cases had a left NRLN. We retrospectively evaluated the patients' imaging studies. Results: An aortic diverticulum was found at the point at which the aberrant LSA originated in the 3 patients with left‐RLNs, but not in the patient with the left‐NRLN. Conclusion: In right‐sided aortic arch + aberrant LSA cases, the absence of an aortic diverticulum suggests a left NRLN. © 2016 Wiley Periodicals, Inc. Head Neck 38: First–E2511, 2016